Pengaruh Kinerja Keuangan, Tata Kelola Perusahaan Dan Penggunaan Derivatif Terhadap Risiko Perusahaan - Candradewi, Made Reina; Rahyuda, Henny (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 13 Nomor 2 Tahun 2019, 2019)
This study aims to determine the effect of financial performance, corporate governance and derivatives usage on firm risk of non-financial companies listed in Kompas100 index at Indonesia Stock Exchange (IDX). This study employs six important independent variables that influence the firm risk, including  liquidity, leverage, profitability, the proportion of independent commissioners and derivatives usage. The population in this study are all non-financial companies listed on the Kompas100 index in 2017 which amounted to 85 companies. This study uses purposive sampling method and the final sample is 74 companies. Data analysis technique used in this study is multiple linear regression analysis. Key research findings in this study indicate that leverage has significant and positive effect on firms risk, profitability has significant and negative effect on firms risk and derivatives usage has negative and significant effect on firms risk.